Fibrinogen Break-Down Products and Clotting Parameters - Gormsen, J; Laursen, B (Thrombosis and Haemostasis, 1967)
Fibrinogen and fibrin break-down products (b. p.) in vitro and in vivo are identified by immunodiffusion, Immunoelectrophoresis and acryl-disc-electrophoresis with immunodiffusion.The clotting parameters obtained in vitro by addition of b. p. to plasma system are compared with similar tests in patients with spontaneous occurence of b. p.B. p. formed after short plasmin digestion of fibrinogen prolong significantly the thrombin time, reduce the maximal thrombin activity in the thrombin generation test and inhibit the clot formation in TEG, increasing the k- and reducing the mA values. These b. p. are further digested. The plasmin resistant fractions exhibiting D or E antigenic properties are less active. The specific activity of the different fractions were not investigated.The clotting parameters in patients with spontaneous occurence of b. p. (D fraction) are very different. Defects similar, but not identical, to those obtained in vitro by addition of b. p. to plasma systems are seen. Accelerated thrombin generation, enhanced fibrin polymerization and accelerated clot formation in TEG are found in others. Similar differences in fibrinolytic activity are demonstrated. The presence of b. p. might be the only abnormality found. B. p. are suggested to develop either as the result of localized thrombo-fibrinolysis or during a more generalized increase in fibrinolytic activity.Immunological methods can demonstrate b. p. in the concentration of 0.05 to 0.10 mg%. The thrombin time is not significantly prolonged until b. p. are present in the concentration of 0.5 mg% (early b. p.) - 2 mg% (later b. p.) as estimated spectrophotometrically.